PERCEPTION ON REWARD SYSTEMAND LEVEL OF MOTIVATION AMONG BUSINESS PROCESS OUTSOURCING EMPLOYEES - Gonzales, Christaine Joy O. (President University, 2024)
This descriptive-correlational study investigated the relationship between BPO employees' perceptions of their company's reward system and their motivation levels in Iloilo City for the fiscal year 2022-2023. It also examined the impact of demographic variables such as age, sex, civil status, and company affiliation. The sample comprised 98 BPO employees selected via convenience sampling. Data were collected using a personal descriptive questionnaire, a custom-designed perception assessment of the reward system, and a modified version of Mullen’s